Sociocultural Adaptation Among University Students in Hungary: The Case of International Students From Post-Soviet Countries - Yerken, Aigerim; Urbán, Róbert; Nguyen Luu, Lan Anh (Journal of International Students, 2022)
With the number of international students increasing worldwide, the sociocultural adaptation difficulties that sojourners face should be addressed adequately. This study explored the sociocultural adaptation of international students (N = 267, Mage = 24.5, SD = 4.7) in Hungary. The exploratory factor analysis of the Sociocultural Adaptation Scale yielded five factors: Affiliative Relations, Bureaucracy and Services, Power Relations, Cultural Understanding, and Academic Performance. The students’ countries of origin (post-Soviet countries versus others) and locations of residence (the capital versus small cities) were determinants of sociocultural adaptation. Depressive symptoms, perceived stress, and lower life satisfaction were associated with greater sociocultural adaptation difficulties. Resilient coping was linked with a lower level of difficulties in academic performance (rs = −.20) and cultural understanding (rs = −.15). Our findings supported that the students’ countries of origin, places of residence, and mental health should be considered in improving counseling and educational programs targeting international students.